Inference, ellipsis and deaccenting - Hardt, Daniel (Proceedings of the Amsterdam Colloquium, 2005)
It is proposed that inference is available for ellipsis interpretation, only when trig gered by a semantically visible violation. This captures well-known observations about available inferences in VP ellipsis, and new observations about unavailable inferences in sluicing. Furthermore, it is argued that inference in deaccenting is gov erned by the same triggering constraint.